Phytochemical Analysis and Antibacterial Activities of Citrullus Lanatus Seed against some Pathogenic Microorganisms (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: citrus lanatus seed; phytochemical analysis; antibacterial activity; pathogenic microorganisms